Prediction of water pollution concentration transport using finite difference methods - Nurul Hanani Johari (Institute of Engineering Mathematics, Universiti Malaysia Perlis, 2017)
The main objective of this study is to predict the water pollution concentration transport. In order to achieve the main objective, the following sub-objectives will be carried out ; to discretize 1D ADE using FTCS and implicit Crank Nicolson method ; to develop a computer algorithm and procedure for solving 1D ADE using MATLAB ; to verify the accuracy of the selected finite difference method in predicting water pollution concentration transport.